Drone testing for 3D reconstruction of massive mounted skeletons in museums: the case of Mammuthus meridionalis (Nesti 1825) from Madonna della Strada (Scoppito, L'Aquila, Italy). (3rd July 2022) - Romano, Marco; Antonelli, Matteo; Palombo, Maria Rita; Rossi, Maria Adelaide; Agostini, Silvano
ABSTRACT: Unmanned aerial vehicles (UAVs), have seen tremendous development in the last decade, with numerous applications in civil and research fields. Drones' success, particularly in the field of research, is due to a number of factors, including rapid technological advancement, tool versatility, and prices that are becoming increasingly affordable even for small research groups or individuals. Given the versatility and ongoing development of micro drones, we tested the use of micro-drones in vertebrate palaeontology to reconstruct mounted skeletons using the photogrammetry method. The experiment was carried out on a massive specimen of Mammuthus meridionalis (Nesti 1825) from Madonna della Strada, which is on display at the east bastion of the Spanish Fortress in L'Aquila (Abruzzo, Central Italy), comparing the results with those obtained using the traditional method using a digital camera. Even though both the traditional digital camera and the drone methods produced a high-resolution 3D model of the skeleton, the results obtained, indeed, lead us to consider the use of micro-drones in museum structures as a very interesting and promising new field of application. Drones provide a simple, fast, and non-invasive system for the study, monitoring, and enhancement of cultural heritage in all of its possible manifestations.